2008
DOI: 10.1111/j.1601-5223.1985.tb00467.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ionizing radiation on chromosome aberrations, sister chromatid exchanges and micronuclei in lymphocytes of smokers and nonsmokers

Abstract: Chromosome aberrations, sister chromatid exchanges and micronuclei were studied in irradiated and unirradiated peripheral blood lymphocytes of smokers and nonsmokers. No effect of smoking could be observed in the number of chromosome aberrations, either in the irradiated or nonirradiated samples. Smokers had significantly elevated SCE values in the unirradiated samples, but the difference in SCE frequencies between smokers and nonsmokers in the irradiated series was not significant. The mean frequency of micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1
1

Year Published

2014
2014
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 19 publications
0
3
1
1
Order By: Relevance
“…HFC evaluation is considered complimentary to SCE analysis, in the assessment of chronic exposures and individual variability in the susceptibility to genotoxic agents (Lazutka 1995, Bonassi et al 1999). According to Stenstrand (1985) smokers had significantly elevated SCE values in unirradiated samples, though SCE frequency differences between smokers and non-smokers in the irradiated series was not significant. Pitarque et al (2002) reported significantly higher mean frequencies of SCE per cell and HFC in smokers compared to non-smokers based on a study of shoe factory workers.…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…HFC evaluation is considered complimentary to SCE analysis, in the assessment of chronic exposures and individual variability in the susceptibility to genotoxic agents (Lazutka 1995, Bonassi et al 1999). According to Stenstrand (1985) smokers had significantly elevated SCE values in unirradiated samples, though SCE frequency differences between smokers and non-smokers in the irradiated series was not significant. Pitarque et al (2002) reported significantly higher mean frequencies of SCE per cell and HFC in smokers compared to non-smokers based on a study of shoe factory workers.…”
Section: Discussioncontrasting
confidence: 46%
“…No effect of smoking could be observed in the number of CA either in irradiated or unirradiated lymphocytes of smokers. The mean frequencies of micronuclei in smokers were significantly higher than non-smokers in a MN study carried out before the advent of CBMN assay and indicated more than an additive effect between smoking and irradiation (Stenstrand 1985). Au et al (1991) also reported slightly higher MN frequencies in smokers and consistently higher translocation frequencies using a challenge assay to assess fidelity of DNA repair after irradiation of lymphocytes.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This study will be the foundation for biological dosimetric analysis with additional research methods such as DC, translocation, and PCC assay. In contrast with DC assay, the fairly radiationspecific analysis, MN assay can be induced by a wide range of confounding factors including smoking, living in heavy air pollution, and exposing to clastogens (Hogstedt and Karlsson 1985, Stenstrand 1985, Prosser et al 1988. Therefore, further studies according to age, gender, and smoking status are required.…”
Section: Discussionmentioning
confidence: 99%
“…Πολλοί ερευνητές υπέθεσαν ότι υψηλά επίπεδα αυτόματων SCEs σχετίζονταν έμμεσα με αυξημένη πιθανότητα ανάπτυξης νεοπλασίας και θεώρησαν ότι οι οικογένειες με υψηλό κίνδυνο εμφάνισης νεοπλασίας, λόγω Πιστεύεται ότι η έκταση της βλάβης στο γενετικό υλικό σε κύτταρα όπως τα λεμφοκύτταρα σχετίζεται με παρόμοια γεγονότα σε κύτταρα στόχους(Mourelatos 1996). Έτσι μπορεί να θεωρηθεί ότι το λεμφοκύτταρο αποτελεί ένα είδος δοσίμετρου που καταγράφει κάθε γονοτοξική επίδραση που δέχεται ο ανθρώπινος οργανισμός(Strenstand 1985, Brown 1988).Γενικά διαπιστώθηκε ότι τα αντινεοπλασματικά φάρμακα που αυξάνουν σημαντικά το επίπεδο των SCEs στα λεμφοκύτταρα των ασθενών που υπόκεινται σε χημειοθεραπεία είναι ιδίως αυτά που συνδέονται με το DNA ή αυτά που προκαλούν δομικές βλάβες στο DNA των…”
unclassified